2001
DOI: 10.1046/j.1365-3083.2001.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Monoclonal Antibodies against Major Antigens of Mycobacterium bovis

Abstract: MPB70 and MPB83 are among the most characteristically exported proteins defining a strongly expressed phenotype of Mycobacterium bovis. These proteins are known to be homologous to osteoblast-specific factor 2. By in vitro culture of mycobacteria they appear to have a limited species distribution and to be relatively specific for M. bovis. Virtually identical genes are however, present in Mycobacterium tuberculosis. In order to facilitate further research into the immunobiology of these proteins and their pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Their reduced expression is due to a point mutation in the translational start codon of the sigK gene [67], observed in many BCG strains, but absent in BCG Moreau. Immunologic studies have shown that both proteins induce cellular and humoral immune responses in experimental models of infection and in natural infection in humans [68,69]. MPB63 is a protein only found in species within the Mtb complex [70], shown to be immunodominant both in humans and animal models [71] and a promising candidate for serodiagnosis of active TB as well as for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Their reduced expression is due to a point mutation in the translational start codon of the sigK gene [67], observed in many BCG strains, but absent in BCG Moreau. Immunologic studies have shown that both proteins induce cellular and humoral immune responses in experimental models of infection and in natural infection in humans [68,69]. MPB63 is a protein only found in species within the Mtb complex [70], shown to be immunodominant both in humans and animal models [71] and a promising candidate for serodiagnosis of active TB as well as for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…From immunologic studies, it is known that both proteins induce cellular and humoral responses in experimental infection of model hosts and natural infection of humans (Miura et al ., 1983; Haslov et al. , 1987; Fifis et al ., 1994; Roche et al ., 1994; Harboe et al ., 1995; Wiker et al ., 1996; Vordermeier et al ., 2000; Lyashchenko et al ., 2001). Based on these observations, both MBP70 and MPB83 have been developed as candidates for novel TB vaccine development (Chambers et al ., 2000; Morris et al ., 2000; Al Attiyah et al ., 2003; Tollefsen et al ., 2003; Xue et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules comprise protein and nonprotein antigens, some of which are conformational in nature and whose threedimensional structure is critical for immune recognition (23). Previously, M. bovis-derived immunogens used to produce antibodies have been whole cells prepared either by heat treatment and sonication or from culture filtrates (13,18,20,31). Heat treatment is detrimental to native, surface epitopes and does not conserve heat-sensitive epitopes, which may partly explain the low diagnostic sensitivity and specificity of antibody tests developed using the antibodies generated during the studies cited above.…”
Section: Discussionmentioning
confidence: 99%